Is data curation education at library and information science schools in North America adequate? - Harris-Pierce, R.L.; Liu, Y.Q. (New Library World, 2012)
Purpose: This study aims to present the results of a survey of library and information science (LIS) schools' websites used to determine if the number of data curation courses offered is adequate to address the needs of the so-called "data deluge". Many authors have identified a gap in the education of LIS students for data curation. Design/methodology/approach: This study surveyed the websites of LIS schools in North America to identify data curation courses. It reviewed and analyzed course descriptions, objectives and syllabi (when available) as well as compared course objectives, requirements, topics, assignments, and projects of the identified courses. Findings: Of the 52 LIS schools in North America's websites examined in this study, 16 institutions offered courses on data curation. The increase in the number of schools offering courses in data curation showed that LIS schools are responding to the demand for data curation professionals. More LIS schools need to add data curation to their curriculum. LIS schools currently offering data curation courses should continue to work together to determine the optimal course objectives and learning outcomes. Originality/value: Although there are several papers focused on particular data curation programs at a few universities, there are no papers that provide an overall view of the status of data curation education in higher education institutions today. This research will be of value and interest to LIS educators and professionals to determine if there is adequate education in place and to identify and evaluate the current state of data curation education. © Emerald Group Publishing Limited.
20 citations (Crossref) [2023-10-31]
Keywords: Digital curation; Digital curation education; Digital librarianship; Digital libraries; Education of information and library science; Information and library school; Information management; dept.ils